English Teachers’ Perception toward Merdeka Curriculum at Junior High Schools in Koto Tangah, Padang - Fatma Fatma; Ratmanida Ratmanida (Universitas Negeri Padang, 2023)
The implementation of Merdeka curriculum brings many change for the teachers. It can influence the teachers’ perceptions toward the implementation of this curriculum. The purpose of this research is to investigate the English teachers’ perception toward the implementation of Merdeka curriculum. Ten English teachers from three Junior High Schools in Koto Tangah, Padang were assigned to complete the questionnaire about their perception of Merdeka curriculum. Quantitative analyses were employed in this research using liker scale approach to measure the questionnaire and calculated the average score. The results showed that the majority of the English teachers had a positive or good perception toward the implementation of Merdeka curriculum with average score 3,1. The teachers agree that it is easy to design the teaching module and they feel convenient using the assessment from Merdeka curriculum. Also, the teachers agree that the implementation of differentiated learning Project based learning link with Pancasila profile and can give a good impact to the students.